One-part and two-part models of nominal Case: Evidence from case distribution - BRATTICO, PAULI (Journal of linguistics, 2010)
In some languages, nominal case is distributed over several adnominal elements, such ademonstrative pronouns, adjectives, participles, numerals and the nominal head itself. In this article, two hypotheses concerning case distribution are compared. According to the TWO-PART MODEL, case assignment to DPs as a whole (determiner phrases or maximal nominal projections) in syntax is based on a different grammatical mechanism than case distribution within those DPs. According to the ONE-PART MODEL, case distribution within DPs and syntactic case assignment to DPs are based on the same case assignment mechanism. Relying upon case distribution data from Finnish, Estonian, Polish, Russian and Serbo-Croatian, this article argues in favor of the onepart model. Furthermore, it is suggested that the one-part case distribution mechanism interacts with two independent morphological principles, one which regulates the overt morphological realization of elements which function as case assigners and another which states that the grammar is subject to a particular type of case hierarchy.